Meningkatkan Kemampuan Mengenal Angka Anak PAUD Nasyithatun Nisa Desa Teluk Kiambang melalui Puzzel Angka - Nita Selviana (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2023)
The ability to recognize numbers is the ability to recognize the concept of numbers and number symbols that become the basis for mastering mathematical concepts. The facts reveal that the ability of most children to recognize numbers is still weak and tends not to develop optimally. It is seen that children do not know numbers correctly. This study aims to find out the ability of group B students of PAUD Nasyithatun Nisa Teluk Kiambang in recognizing numbers before and after using puzzles number. This belonged to the Class Action Research (CAR), with 12 subjects. Data was collected through tests, observations, and field notes; and analyzed descriptively. The findings stated that children’s ability to recognize numbers were at 36.66% (pre-cycle), 58.32% (cycle I), and 86.66% (cycle II). Thus, these confirm that the media of puzzles number can improve children’s ability to recognize numbers. In addition, the enthusiasm of the children increases and the learning atmosphere is more fun.